2011
DOI: 10.1128/jvi.05478-11
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sequences in a Protein (ORF2) Encoded by the Latency-Related Gene of Bovine Herpesvirus 1 That Inhibits Apoptosis and Interferes with Notch1-Mediated trans -Activation of the bICP0 Promoter

Abstract: Bovine herpesvirus 1 (BHV-1) infection induces clinical symptoms in the upper respiratory tract, inhibits immune responses, and can result in life-threatening secondary bacterial infections. Following acute infection, BHV-1 establishes latency in sensory neurons within trigeminal ganglia. Periodically, reactivation from latency occurs, resulting in virus transmission. The latency-related (LR) RNA is abundantly expressed in latently infected sensory neurons, suggesting that LR gene products regulate the latency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 78 publications
(89 reference statements)
3
44
0
Order By: Relevance
“…4B). As previously reported (6,7,28), ORF2 was primarily localized at the rim of the nucleus (Fig. 4C).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…4B). As previously reported (6,7,28), ORF2 was primarily localized at the rim of the nucleus (Fig. 4C).…”
supporting
confidence: 87%
“…ORF2 contains a nuclear localization signal (NLS) (Fig. 8A) that, when deleted (the ORF2ΔNLS mutant), expresses a protein that localizes to the plasma membrane (28). The ORF2ΔNLS mutant was not able to enhance ␤-catenindependent transcription more effectively than the empty vector.…”
mentioning
confidence: 99%
“…To induce neurite sprouting, 24 h after transfection, cells were seeded into new plates at a low density of 2,000/cm 2 and starved in medium with 0.5% serum for 3 days. Cells were then fixed and stained, and a ␤-galactosidase (␤-Gal) assay was performed as previously described (44) Dual-luciferase reporter assay. Neuro-2A cells (8 ϫ 10 5 ) were seeded into 60-mm dishes containing EMEM with 10% FCS at 24 h prior to transfection.…”
Section: Cellsmentioning
confidence: 99%
“…ORF2 stably interacts with Notch3 or Notch1, and these interactions impair the ability of Notch to stimulate viral gene expression and productive infection (26,44). Although these studies indicated that ORF2 interferes with the ability of Notch family members to stimulate viral promoters and productive infection, they did not address whether ORF2 influences activated Notch in the context of known cellular functions.…”
Section: Expression Of Notch and Orf2 In Tg During The Latency-reactimentioning
confidence: 99%
See 1 more Smart Citation